2021
DOI: 10.3390/ani11102944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Probiotics, Prebiotics and Synbiotics Injected in Ovo on the Microstructure of the Breast Muscle in Different Chicken Genotypes

Abstract: The aim of the study was to analyse the effect of probiotics, prebiotics and synbiotics injected in ovo on day 12 of embryonic development on the microstructure of the superficial pectoral muscle (musculus pectoralis superficialis) from 42-day-old chickens of different genotypes: broilers (Ross 308) and general-purpose type (green-legged partridge (GP) chickens Zk-11, native chickens). Incubated eggs were divided into four groups (each genotype separately) depending on the substance injected in ovo: normal sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Although probiotics have not been previously evaluated for their effects on embryonic muscle development in chicken, in ovo supplementation of synbiotics was shown to have no effect on muscle fiber number or CSA in adult Ross 308 birds ( Stasiak et al, 2021 ). However, supplementation of nutrients including L-glutamine, insulin-like growth factor I, silver nanoparticles, and nicotinamide riboside to embryos resulted in improved MFD ( Liu et al, 2012 ; Grodzik et al, 2013 ; Gonzalez and Jackson, 2020 ; Husseiny et al, 2021 ; Xu et al, 2021a ).…”
Section: Resultsmentioning
confidence: 99%
“…Although probiotics have not been previously evaluated for their effects on embryonic muscle development in chicken, in ovo supplementation of synbiotics was shown to have no effect on muscle fiber number or CSA in adult Ross 308 birds ( Stasiak et al, 2021 ). However, supplementation of nutrients including L-glutamine, insulin-like growth factor I, silver nanoparticles, and nicotinamide riboside to embryos resulted in improved MFD ( Liu et al, 2012 ; Grodzik et al, 2013 ; Gonzalez and Jackson, 2020 ; Husseiny et al, 2021 ; Xu et al, 2021a ).…”
Section: Resultsmentioning
confidence: 99%
“…Bacillus amyloliquefaciens CGMCC18230 supplementation improved tibial bone mineralization and growth performance by increasing the relative abundances of Ruminococcaceae (butyrate-producing), Akkermansia (polyamine-producing), and Alistipes (polyamine-producing) ( Li et al ., 2022 ). Previous studies have also shown that probiotics exert beneficial effects on the muscle growth of broiler chickens ( Shah et al , 2019 ; Stasiak et al , 2021 ). Dietary supplementation with Enterococcus faecium AL41 increased the number of myonuclei per fiber, improved capillarization, and further improved body weight owing to the high intramuscular expression of IGF-1 and lowered MYF5 expression in broilers ( Albrecht et al , 2022 ).…”
Section: Beneficial Properties and Applications Of Probiotics In Chic...mentioning
confidence: 96%
“…The supplementation of Lactococcus lactis subsp. cremoris (10 5 cfu/egg), Bi 2 tos (3.5 mg/egg), or Bi 2 tos (3.5 mg/egg) with Lactococcus lactis (10 5 cfu/egg) injected into the air chamber on e12 showed no effects on muscle microstructure (fiber diameter, normal fiber, fiber atrophy, giant fiber, change in fiber shape, necrotic fiber, and fiber splitting) ( 79 ). The supplementation of arginine at different concentrations (6.25, 25, and 100 mg/kg) on e16 stimulated myoblast differentiation but reduced the number of myofibers and the subsequent muscle growth during the post-hatch period ( 80 ).…”
Section: Muscle Development and Meat Qualitymentioning
confidence: 99%